Implementation Of Continuous Midwifery Care In Maternal Health Services - Fyzria Qudratullah; Eka Sarofah Ningsih (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Continuity midwifery care of midwifery Continuous midwifery care (CNC) is a midwifery service approach provided continuously from pregnancy, childbirth, postpartum, to family planning services. This approach aims to improve the quality of maternal health services and reduce the risk of maternal complications. This study aims to determine the implementation of continuous midwifery care in maternal health services. The study used quantitative methods with an analytical design and a cross-sectional approach. Sectional. The research sample was mothers who received midwifery services at health service facility X. Data were collected using questionnaires and observation sheets, then analyzed using the Chi- Square test. The results of the study showed that the implementation of continuous midwifery care was significantly related to the improvement of the quality of maternal health services (p < 0.05). The conclusion of this study is that continuous midwifery care plays an important role in improving the quality of maternal health and service.